2011
DOI: 10.1080/00207543.2010.504754
|View full text |Cite
|
Sign up to set email alerts
|

The configuration of design and manufacture knowledge models from a heavyweight ontological foundation

Abstract: Problems related to knowledge sharing in design and manufacture, for supporting automated decision-making procedures, are associated with the inability to communicate the full meaning of concepts and their intent within and across system boundaries. To remedy these issues, it is important that the explicit structuring of semantics, i.e. meaning in computation form, is first performed and that these semantics become sharable across systems. This paper proposes a Common Logic-based ontological foundation as a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Prior work [6,7,15] has demonstrated that an ontology of well-defined core concepts can serve as a foundation for the sufficiently flexible development of domain-specific concepts, such as those pertinent to feature-based design and manufacturing planning viewpoints. Thus, the IMKS approach allows the derivation of specialised knowledge bases as repositories for designers and planners alike, without the need to commit to a fixed master model.…”
Section: Ontologies Of Core Conceptsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior work [6,7,15] has demonstrated that an ontology of well-defined core concepts can serve as a foundation for the sufficiently flexible development of domain-specific concepts, such as those pertinent to feature-based design and manufacturing planning viewpoints. Thus, the IMKS approach allows the derivation of specialised knowledge bases as repositories for designers and planners alike, without the need to commit to a fixed master model.…”
Section: Ontologies Of Core Conceptsmentioning
confidence: 99%
“…Thus, the IMKS approach allows the derivation of specialised knowledge bases as repositories for designers and planners alike, without the need to commit to a fixed master model. In that sense, the heavyweight ontology dimension of this work builds on top of the current perceived advantages of applying formal ontologies within a PLM context to aid the process of semantic interoperability and knowledge exchanges [3,6,7,16,17].…”
Section: Ontologies Of Core Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…A typical manufacturing facility has a centralised database containing the product data model (PDM), which holds information on the product [1], and the manufacturing data model (MDM), which holds information on the systems needed to manufacture the product [2]. Together, the PDM and MDM provide an optimal scheduling plan for all control subsystems [3], organised hierarchically (e.g., as factories, cells, and stations) through a central host computer.…”
Section: Introductionmentioning
confidence: 99%